In search of happiness (Journal of Parents and Teachers, 2012)
This film allow us to think about different topics such as family, couple (distribution of tasks, conflict in the couple and lack of confidence), parents/child relationship, autoesteem, the value of effort and money and happiness. This article also shows practical activities for students of secondary education, vocational education and Highschool. In adittion, it  gives a technical specification sheet and an overview of the film as well as some curiosities about the actors and the film itself. -EndFragment--> nte en el campo de la música religiosa, formando con María Barcea el Grupo CoMpaSIóN, que ya ha publicado los discos “Navidad Actual” editada por PPC. Autor del libro Religión y Música Actual (PPC, 2011), también como músico está presente en el campo de la música religiosa, formando con María Barcea el Grupo CoMpaSIóN, que ya ha publicado los discos “Navidad Actual” (2008) y “Caminamos con Jesús” (2011), además del material musical para el proyecto educativo de Infantil y Primaria “Javerim”, todo ello con la editorial San Pablo.
Keywords: Couple; Family; Autoesteem; Selfefficiency; Effort; Happiness; cinema and education